Dazomet changes microbial communities and improves morel mushroom yield under continuous cropping - Chen, Bo; Shao, Gaige; Zhou, Tao; Fan, Qinghao; Yang, Nuolin; Cui, Man; Zhang, Jinwei; Wu, Xiangli; Zhang, Bangxi; Zhang, Ruiying (Frontiers in Microbiology, 2023)
Morels (Morchella spp.) are highly prized and popular edible mushrooms. The outdoor cultivation of morels in China first developed at the beginning of the 21st century. Several species, such as Morchella sextelata, M. eximia, and M. importuna, have been commercially cultivated in greenhouses. However, the detriments and obstacles associated with continuous cropping have become increasingly serious, reducing yields and even leading to a complete lack of fructification. It has been reported that the obstacles encountered with continuous morel cropping may be related to changes in the soil microbial community. To study the effect of dazomet treatment on the cultivation of morel under continuous cropping, soil was fumigated with dazomet before morel sowing. Alpha diversity and beta diversity analysis results showed that dazomet treatment altered the microbial communities in continuous cropping soil, which decreased the relative abundance of soil-borne fungal pathogens, including Paecilomyces, Trichoderma, Fusarium, Penicillium, and Acremonium, increased the relative abundance of beneficial soil bacteria, including Bacillius and Pseudomonas. In addition, the dazomet treatment significantly increased the relative abundance of morel mycelia in the soil and significantly improved morel yield under continuous cropping. These results verified the relationship between the obstacles associated with continuous cropping in morels and the soil microbial community and elucidated the mechanism by which the obstacle is alleviated when using dazomet treatment.